A review of chemosensory perceptions, food preferences and food-related behaviours in subjects with Prader–Willi Syndrome. (1st April 2016) - Martínez Michel, Lorelei; Haqq, Andrea M.; Wismer, Wendy V.
Abstract: Hyperphagia and obsessive preoccupation with food are hallmark characteristics of Prader–Willi Syndrome (PWS). Although hyperphagia in PWS is linked to hypothalamic dysfunction, the underlying mechanisms behind this problem are poorly understood. Moreover, our understanding of how chemosensory perceptions and food choice/preferences relate to hyperphagia in individuals with PWS is very limited. This narrative review synthesizes studies that assessed chemosensory perceptions, food choices and food-related behaviours in PWS individuals and highlights knowledge gaps in research for further exploration. Twenty seven publications from relevant databases met inclusion criteria and were organized thematically by study technique in the review. Results suggested that PWS individuals have consistent preferences for sweet tastes and in most studies have exhibited a preference for calorie-dense foods over lower calorie foods. No firm conclusions were drawn concerning the chemosensory perceptions of PWS individuals and their influence on food preferences or choices; chemosensation among PWS individuals is an understudied topic. Current evidence suggests that eating behaviour in PWS is a complex phenomenon that involves a dysfunctional satiation and not excessive hunger. Food preferences, choices, and related behaviours and the impact of these on obesity management in those with PWS remain poorly understood and require further study using validated tools and methodologies.